2018
DOI: 10.1111/os.12404
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Plus Low‐dose Epinephrine Reduces Blood Loss in Total Knee Arthroplasty: A Systematic Review and Meta‐analysis

Abstract: The present study assessed the effectiveness of the combined administration of tranexamic acid (TXA) plus low‐dose epinephrine in primary total knee arthroplasty (TKA). We searched the following Chinese electronic databases: China National Knowledge Infrastructure and WanFang Data. We also searched the following English electronic databases: PubMed, Embase, Web of Science, and Central Register of Controlled Trials. To search for additional eligible studies, we also used Google's search engine. All randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Hunt et al estimated a reduction of 120,000 deaths worldwide each year if TXA was given to all patients with severe traumatic bleeding ( Hunt, 2015 ). TXA was also demonstrated to be a safe and effective choice in total knee arthroplasty (TKA), total hip arthroplasty (THA), cardiac surgery, and other types of surgeries ( Wu et al, 2018 ; Zhang Y. et al, 2019 ; Sukeik et al, 2020 ). Moreover, TXA has also been reported in treating postpartum hemorrhage ( Novikova et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hunt et al estimated a reduction of 120,000 deaths worldwide each year if TXA was given to all patients with severe traumatic bleeding ( Hunt, 2015 ). TXA was also demonstrated to be a safe and effective choice in total knee arthroplasty (TKA), total hip arthroplasty (THA), cardiac surgery, and other types of surgeries ( Wu et al, 2018 ; Zhang Y. et al, 2019 ; Sukeik et al, 2020 ). Moreover, TXA has also been reported in treating postpartum hemorrhage ( Novikova et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zubairi et al[ 21 ] also demonstrated that epinephrine was effective in reducing the amount of blood loss and transfusion needs in the surgical treatment of knee contracture. Wu et al[ 22 ] reported that epinephrine together with tranexamic acid decreased blood loss in total hip arthroplasty. In the literature, the use of epinephrine in the field of orthopedic surgery involves the studies conducted in the adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al [ 17 ] from our institution has proved that TKA patients treated with multiple doses of intravenous and topical TXA had less hidden blood loss, better knee function recovery, and better early satisfaction than controlled patients. Multiple doses of intravenous TXA application can prevent systemic plasminogen activation and delay fibrinolysis, which can result in intraoperative blood loss and postoperative hidden blood loss reduction [ 18 ]. Compared with intravenous TXA, topical application can provide a maximum concentration of TXA at the bleeding site, lower TXA absorption, reduce limb swelling, and improve wound-healing [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%